Pengaruh Biaya Operasional dan Biaya Produksi Terhadap Profitabilitas pada PDAM Tirta Terubuk Kabupaten Bengkalis - Erlindawati, Erlindawati; Jandriyani, Rina; Mashuri, Mashuri; Oktayani, Dewi (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the effect of operational costs and production costs on the profitability of the Regional Drinking Water Company (PDAM) Tirta Terubuk in Bengkalis Regency. Profitability in this research is measured using the Return on Assets (ROA) indicator. The background of this study is based on the importance of cost management in improving operational efficiency and effectiveness, especially for region-owned enterprises that provide public services. This research uses a quantitative approach with multiple linear regression analysis.The data used are secondary data obtained from the financial statements of PDAM Tirta Terubuk Bengkalis for the period 2022 to 2024. The results show that partially, both operational costs and production costs have a negative and significant effect on profitability. Simultaneously, these two independent variables contribute 65,6% to the variation in the company’s profitability. These findings align with cost efficiency theory and previous studies which state that an increase in costs, if not accompanied by effective management, can reduce the company’s net profit. Therefore, PDAM is advised to implement more optimal cost control strategies to maintain the sustainability and financial performance of the company.